Advanced information systems engineering : 24th International conference, CAiSE 2012, Gdansk, Poland, June 25-29, 2012. Proceedings - Ralyté, Jolita (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 24th International Conference on Advanced Information Systems Engineering, CAiSE 2012, held in Gdansk, Poland, in June 2012. The 42 revised full papers, 2 full-length invited papers and 4 short tutorial papers, were carefully reviewed and selected from 297 submissions. The contributions have been grouped into the following topical sections: business process model analysis; service and component composition; language and models; system variants and configuration; process mining; ontologies; requirements and goal models; compliance; monitoring and prediction; services; case studies; business process design; feature models and product lines; and human factors.